Language skills and employment rate of refugees in Germany improving with time - Herbert Brücker; Johannes Croisier; Yuliya Kosyakova; Hannes Kröger; Giuseppe Pietrantuono; Nina Rother; Jürgen Schupp (DIW Weekly Report, 2019)
Asylum seekers migrating to Germany remains a hotly debated topic. The second wave of a longitudinal survey of refugees shows that their integration has progressed significantly, even though some refugees came to Germany in poor health and with little formal education. Compared to the previous year, refugees' German skills have improved, as have their participation rates in the workforce, education, and training.
Keywords: E24; I14; I24; 330; refugees; labour market integration; language skills; health status